Individualized Opioid Titration for Complex Symptom Management in Terminally Ill Cancer Patients Receiving Home Hospice Care: A Prospective Cohort Study - Kunihiko Watanabe; Kumi Tochimura; Hiromi Fujita; Yukie Kushima; Kazuhiko Kushima; Yuki Kamiyama; Akemi Hemmi (American Journal of Hospice and Palliative Medicine®, 2026)
Background Individualized opioid titration is recommended for symptom management in patients with advanced cancer, but prospective data from home hospice care remain limited. We evaluated individualized opioid titration in terminally ill cancer patients receiving physician-led home hospice care. Methods This prospective observational study included 501 consecutive terminally ill cancer patients who died under the care of a home hospice clinic between January 2020 and December 2025. Opioids were prescribed for cancer-related pain and other opioid-responsive symptoms. When oral administration became difficult, continuous subcutaneous infusion with patient-controlled analgesia (PCA) was used. Final opioid type, route of administration, oral morphine equivalent daily dose (MEDD), and ketamine use were analyzed. Results Opioids were administered to 490 patients (97.8%). Continuous subcutaneous infusion was the final route in 437 patients (89.2%). Morphine was the most frequently prescribed opioid (70.4%), followed by hydromorphone (22.2%) and oxycodone (7.1%). Final MEDDs ranged from 10 to 6000 mg/day, demonstrating substantial interindividual variability. Patients aged ≤64 years required significantly higher MEDDs than those aged ≥65 years ( P < 0.001), whereas opioid requirements did not differ significantly according to primary cancer site ( P = 0.103). Ketamine was required in only 11 patients (2.2%). Conclusions Terminally ill cancer patients receiving home hospice care showed marked interindividual variability in opioid requirements. These findings support repeated bedside assessment and individualized opioid titration rather than predetermined dose limits or primary cancer site as the cornerstone of patient-centered symptom management.